Lupus anticoagulant laboratory diagnosis by applying the 2020 ISTH-SSC guidelines. Issue 224 (April 2023) - Talon, L.; Fourneyron, V.; Senectaire, S.; Tardieu, M.; Tillier, M.; Trapani, A.; Trayaud, A.; Vaissade, A.; Sapin, A.F.; Lebreton, A.; Sinegre, T.
Abstract: Background: The ISTH-SSC guidelines for lupus anticoagulant (LA) testing recommend using in-house determined cut-off values, pooled normal plasma (PNP) for ratio normalization, and a ratio for the mixing test interpretation. They strongly support the mixing step role in the diagnostic process. Objectives: To investigate and compare the LA testing results and interpretations obtained following the ISTH-SSC guidelines or the available alternatives. Patients/methods: Blood samples for LA testing from 462 consecutive patients were evaluated for screening, mixing and confirmatory tests. The analysis focused on the interpretation differences between using (1) the in-house cut-off values versus the manufacturer's cut-off values, (2) a normalized ratio calculated using PNP at each run versus the mean of the reference interval, (3) a normalized ratio versus the index of circulating anticoagulant to interpret the mixing step, and (4) a two-step versus three-step procedure. Results: LA testing outcomes were comparable when using the in-house and manufacturer's cut-off values. More positive dilute Russell's viper venom (DRVV) time results were obtained with the normalized ratio based on PNP than with the mean of the reference interval. Overall, the mixing test results obtained with the normalized ratio and the index of circulating anticoagulant showed a good agreement. Among the 97 DRVV Screen test-positive samples, 33 and 89 were classified as LA-positive with the 3-step and the 2-step procedure, respectively. Conclusions: The cut-off value used and the way to normalize ratios had a limited impact. Conversely, it is important to understand the mixing test characteristics to maximize its diagnostic potential. Graphical abstract: Unlabelled Image Highlights: The current ISTH-SSC guidelines for LA testing aim to harmonize practices. However, methodologies are not always consistent and alternatives are possible. The impact of the cut-off value used and the way to normalize ratios remained limited. It is important to understand the mixing test characteristics.